2017
DOI: 10.1093/annweh/wxw021
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Bisphenol A (BPA) Concentrations among Workers in Industries that Manufacture and Use BPA in the USA

Abstract: Background Bisphenol A (BPA) toxicity and exposure risk to humans has been the subject of considerable scientific debate; however, published occupational exposure data for BPA are limited. Methods In 2013–2014, 77 workers at six US companies making BPA, BPA-based resins, or BPA-filled wax provided seven urine samples over two consecutive work days (151 worker-days, 525 samples). Participant information included industry, job, tasks, personal protective equipment used, hygiene behaviors, and canned food/bever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 48 publications
1
34
1
Order By: Relevance
“…Among the most common endocrine disruptors, bisphenol A (BPA), used in epoxy resins and polycarbonate plastics, has been detected in biological fluids of most of the population worldwide, essentially due to oral contamination by ingestion of BPAcontaining food and drinks (Pirard et al, 2012;Galloway et al, 2018). Epidemiological and experimental studies show that human BPA serum concentrations generally vary from 0.2 to 1.6 ng/mL −1 (0.88 to 7 nM), but may reach higher values in workers who manipulate high amounts of BPA (thermal paper or plastics industries) (Hines et al, 2017). Many adverse health effects, such as hyperactivity, obesity, fertility problems, enamel defects, and cardiac arrhythmia have been associated with exposure to BPA, especially during the perinatal period of life (Jedeon et al, 2013) (reviewed in Giulivo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Among the most common endocrine disruptors, bisphenol A (BPA), used in epoxy resins and polycarbonate plastics, has been detected in biological fluids of most of the population worldwide, essentially due to oral contamination by ingestion of BPAcontaining food and drinks (Pirard et al, 2012;Galloway et al, 2018). Epidemiological and experimental studies show that human BPA serum concentrations generally vary from 0.2 to 1.6 ng/mL −1 (0.88 to 7 nM), but may reach higher values in workers who manipulate high amounts of BPA (thermal paper or plastics industries) (Hines et al, 2017). Many adverse health effects, such as hyperactivity, obesity, fertility problems, enamel defects, and cardiac arrhythmia have been associated with exposure to BPA, especially during the perinatal period of life (Jedeon et al, 2013) (reviewed in Giulivo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to BPA is almost universal in the United States; over 90% of the U.S. population has detectable levels of urinary BPA (Calafat et al 2008). Diet is the primary route of exposure, although exposure may also occur via inhalation and dermal absorption, particularly in occupational settings (Ehrlich et al 2014; Hehn 2016; Li et al 2010; Hines et al 2017; Thayer et al 2015b; Von Goetz et al 2010; Zalko et al 2011). BPA is capable of binding to the membrane and nuclear estrogen receptors and can affect gonadal hormone signaling, which play critical roles in the developing brain, influencing pathways that lead to sex-specific development and behavior (Henrichs et al 2013; Schug et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The 5 mg/kg BPA is chosen as a starting dose, since it is a no‐observed‐adverse‐effect level (NOAEL) . In view of the high dose, BPA as high as 250–500 mg/kg were used in several animal studies and BPA detectable level in occupational individuals were reported to be 70 times higher than in general population . In the present study, however, BPA at the maximum of 50 mg/kg is selected as it has been reported to induce oxidative and mitochondrial injury to a certain extent .…”
Section: Methodsmentioning
confidence: 99%
“…16 In view of the high dose, BPA as high as 250-500 mg/kg were used in several animal studies 10,17 and BPA detectable level in occupational individuals were reported to be 70 times higher than in general population. 18 In the present study, however, BPA at the maximum of 50 mg/kg is selected as it has been reported to induce oxidative and mitochondrial injury to a certain extent. 3 A dose and regimen of NAC is based on a study showing its potential to restore cognitive dysfunction and oxidative stress induced by BPA.…”
Section: Experimental Designmentioning
confidence: 99%